2018
DOI: 10.1177/0954406218784317
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of aerodynamic effects of opposite wrap-around fins at supersonic speeds

Abstract: In this research work, using numerical simulations, the three-dimensional flow around a standard projectile is investigated with two fin arrangement models, namely opposite and conventional wrap-around fins. Eliminating the rolling moment and investigation of aerodynamic performance of the new geometries are the purpose of this paper. Finite volume method is used to undertake the numerical simulations where flow is considered to be compressible, steady, nonviscous, and three-dimensional. For this purpose, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The validation of these simulations, for the results from Mach ∼2.7-3.0 M, were extended to the drag and rolling moment coefficients obtained by other wind tunnel and computational research studies as well (Dahlke and Craft, 1973; Fournier, 1977; Vitale et al , 1992; Edge, 1994; McIntyre et al , 1998; Paek et al , 1999; Mao et al , 2007; Liu et al , 2013; Li et al , 2015; Bagheri et al , 2018). The drag coefficient vs Mach number graph (Figure 16) show a general trend of decreasing with an increase in Mach number.…”
Section: Verification and Validationmentioning
confidence: 96%
See 1 more Smart Citation
“…The validation of these simulations, for the results from Mach ∼2.7-3.0 M, were extended to the drag and rolling moment coefficients obtained by other wind tunnel and computational research studies as well (Dahlke and Craft, 1973; Fournier, 1977; Vitale et al , 1992; Edge, 1994; McIntyre et al , 1998; Paek et al , 1999; Mao et al , 2007; Liu et al , 2013; Li et al , 2015; Bagheri et al , 2018). The drag coefficient vs Mach number graph (Figure 16) show a general trend of decreasing with an increase in Mach number.…”
Section: Verification and Validationmentioning
confidence: 96%
“…The aerodynamics of flow around the fin and the fin passage (area between the adjoining fins) have been examined again and again for improvement. It has been illustrated that at 0° angle of attack the pressure on both sides of the fins is different (Bagheri et al , 2018). The flow is influenced by the fin leading and trailing edge, and thus, many research studies have been carried out on them previously.…”
Section: Introductionmentioning
confidence: 99%
“…The fin drag comparison, between the planar and the wrap-around, showed that the WAFs had 10% higher value as that of the planar fins. In the past, numerous numerical studies (Bagheri, Pasandidehfard, & Tavakoli Sabour 2018;Li, Abbas, & Rui, 2015;Krishna, Surit, Kushari, & Ghosh, 2009;Eidell, Nance, McGowan, Carpenter, & Moore, 2012;Murman, 2007) have been performed on planar and wrap-around finned missiles which have used inviscid, viscid and turbulent flow conditions. However, most of these studies were performed on a complete missile body with four fins, these studies form the basis of implying turbulence modelling to the current model.…”
Section: Introductionmentioning
confidence: 99%